3D photography is a reliable burn wound area assessment tool compared to digital planimetry in very young children. Issue 6 (September 2015) - Gee Kee, E.L.; Kimble, R.M.; Stockton, K.A.
Highlights Burns ≤10% TBSA in children measured using Visitrak™ and 3D photography. Measurements taken by one investigator and level of agreement calculated. 3D photography a reliable alternative to Visitrak™ in children with burns. 3D photography is a suitable for children under the age of 3 years than Visitrak™.